Concurrent Hepatic Artery and Portal Vein Thrombosis after Orthotopic Liver Transplantation with Preserved Allografts - Arshad Khan; P. Park; Jose Oberholzer; Ivo Tzvetanov; Raquel Garcia Roca; Ron C. Gaba; Enrico Benedetti; Hoonbae Jeon (Case Reports in Transplantation)
In contrast to early HAT, late HAT has an insidious clinical presentation. Nevertheless, biliary and vascular reconstructions in this late setting are unlikely to improve outcome. Patent portal flow makes an important contribution to the viability of liver in case of late HAT while the allograft reconstitutes intrahepatic arterial flow through neovascularization. Concurrent HAT with PVT without immediate graft necrosis is extremely rare, and allograft and patient survival are seemingly impossible without retransplantation. In fact, hepatopetal arterial and portal venous neovascularization are known albeit obscure phenomena that can preserve posttransplant hepatic function under the extenuating circumstances of complete interruption of blood flow to the graft. We describe two such cases that developed combined HAT and PVT more than six months after OLT with perfect preservation of graft function. The survival of allografts in our cases was due to extensive hepatopetal arterial and portal venous collateralization. Simultaneous HAT and PVT after OLT are rare events and almost uniformly fatal, if they occur early. Due to paucity of such cases, however, underlying mechanisms and etiology remain elusive, and despite radiological diagnosis of these complications, there is no way to predict these events in the wake of stable graft function.